2020
DOI: 10.1177/2010105820964829
|View full text |Cite
|
Sign up to set email alerts
|

Adult malnutrition, nutritional interventions and outcomes in Singapore: a scoping review of local studies for the past 20 years

Abstract: Background: There is currently no review published on the prevalence and incidence of malnutrition in Singapore across various populations, or what interventions or policies are in place for preventing/treating malnutrition. Objectives: This review aims to determine the: (a) incidence and prevalence of malnutrition in the community, and in acute, intermediate and long-term care facilities; (b) interventions implemented for screening, assessing and treating/preventing malnutrition; (c) specific clinical populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(198 reference statements)
0
0
0
Order By: Relevance
“…Recent studies have reported a similar prevalence of malnutrition in hospitalised patients today to what there was then: 14.0-32.3% among surgical patients [4,5], 22.6-50.0% among patients with cancer [4,[6][7][8][9], and 38.0-78.0% among ICU patients [10,11]. While national prevalence data in Singapore are limited, a recent scoping review of local studies reported a malnutrition prevalence of 14.7-65.0% in acute care settings [12]. Among hospitalised older patients (≥65 years) in Singapore, about 35.0% were malnourished at admission [13].…”
Section: Introductionmentioning
confidence: 73%
“…Recent studies have reported a similar prevalence of malnutrition in hospitalised patients today to what there was then: 14.0-32.3% among surgical patients [4,5], 22.6-50.0% among patients with cancer [4,[6][7][8][9], and 38.0-78.0% among ICU patients [10,11]. While national prevalence data in Singapore are limited, a recent scoping review of local studies reported a malnutrition prevalence of 14.7-65.0% in acute care settings [12]. Among hospitalised older patients (≥65 years) in Singapore, about 35.0% were malnourished at admission [13].…”
Section: Introductionmentioning
confidence: 73%
“…DALYs were used for this CCA instead of the more commonly known quality-adjusted life years (QALYs), which focus more on quality of life and treatment outcomes [13]. Hence, QALYs may not adequately capture the long-term and multifaceted nature of malnutrition's impact, particularly in vulnerable populations, where the disease burden manifests through a combination of premature mortality and long-term disability [22].…”
Section: Discussionmentioning
confidence: 99%
“…The CCA indicated that 28.15 disability-adjusted life years (DALYs) were averted across the Singapore Health Services' (SingHealth, Singapore) institutions of Singapore General Hospital, Changi General Hospital, and Seng Kang General Hospital due to the successful treatment or prevention of malnutrition by dietitians from 1 April 2021 to 31 March 2022. This was based on an estimated 45,000 patients (from existing data, 27% of patients were on oral nutrition with malnutrition) [21,22], with 68% (range: 53% to 83%) of the malnourished patients returning to a well-nourished state after treatment [19,20].…”
Section: Consequences (Clinical Outcomes)mentioning
confidence: 99%